Poligami Dalam Perspektif Hadis: (Telaah Hadis Tematik) - Lisanatul Layyinah (El Nubuwwah Jurnal Studi Hadis, 2023)
Polygamy is a problem that has not been discussed until now. With people’s understanding and knowledge, this resulth in a narrow understanding of several arguments (The Qur’an and Hadith) regarding polygamy. At Least, there are two views regarding polygamy, namely; first, allowing polygamy under certain conditions; secondly, its prohibits polygamy, because of a fatal disadvantag. This study aims to discuss the hadith about polygamy it is prohibition. This reseach method is qualitative, using the qualitative analysis approach , namelu the author explains from the aspect of polygamy in general in islam and the examines specifically polygamy in thr view of polygamous scholars, polygamy in the perspective of hadith and analysis hadith with takhrijul hadith methoud. The resulth of this reseach include the views general opinion on polygamy, the arguments of the al-Qur’an and Hadith on polygamy, Takhrij Hadith , and the views of the ulama’ on the verses of the al-Qur’an and hadith on polygamy. The conclusion of this study is that vplygamy is something that was present before islam was present. And since Islam came into existence, polygamy has begun to be regulated and a very noble and humane way from the point of view of different scholars’ as well as state laws. And the Takhrijul Hadith method is very importhant in reviewing the various hadith arguments about polygamy in order to strengthen the oblique issue of polygamy’s basic priciples. The prohibition of polygamy is expressly intented to maintain the status of women.